Association between bacterial vaginosis and cervical intraepithelial neoplasia: systematic review and meta-analysis. - Evy Gillet; Joris F A Meys; Hans Verstraelen; Rita Verhelst; Philippe De Sutter; Marleen Temmerman; Davy Vanden Broeck (PLoS ONE)
Objective Bacterial vaginosis (BV), the most common vaginal disorder among women of reproductive age, has been suggested as co-factor in the development of cervical cancer. Previous studies examining the relationship between BV and cervical intra-epithelial neoplasia (CIN) provided inconsistent and conflicting results. The aim of this study is to clarify the association between these two conditions. Methods A systematic review and meta-analysis were conducted to summarize published literature on the association between BV and cervical pre-cancerous lesions. An extensive search of electronic databases Medline (Pubmed) and Web of Science was performed. The key words 'bacterial vaginosis' and 'bacterial infections and vaginitis' were used in combination with 'cervical intraepithelial neoplasia', 'squamous intraepithelial lesions', 'cervical lesions', 'cervical dysplasia', and 'cervical screening'. Eligible studies required a clear description of diagnostic methods used for detecting both BV and cervical pre-cancerous lesions. Publications were included if they either reported odds ratios (OR) and corresponding 95% confidence intervals (CI) representing the magnitude of association between these two conditions, or presented data that allowed calculation of the OR. Results Out of 329 articles, 17 cross-sectional and 2 incidence studies were selected. In addition, two studies conducted in The Netherlands, using the national KOPAC system, were retained. After testing for heterogeneity and publication bias, meta-analysis and meta-regression were performed, using a random effects model. Although heterogeneity among studies was high (χ(2) = 164.7, p<0.01, I(2) = 88.5), a positive association between BV and cervical pre-cancerous lesions was found, with an overall estimated odds ratio of 1.51 (95% CI, 1.24-1.83). Meta-regression analysis could not detect a significant difference between studies based on BV diagnosis, CIN diagnosis or study population. Conclusions Although most studies were cross-sectional and heterogeneity was high, this meta-analysis confirms a connection between BV and CIN.